Login

Register Now

Lorem ipsum dolor sit amet, consectetur adipiscing elit. Morbi adipiscing gravdio, sit amet suscipit risus ultrices eu. Fusce viverra neque at purus laoreet consequa. Vivamus vulputate posuere nisl quis consequat.

Register Now

Lost Password

Lost your password? Please enter your username and email address. You will receive a link to create a new password via email.

2x - 3y = 9; 2x + y = 13

2x - 3y = 9; 2x + y = 13

Print or Save
2x - 3y = 9 ... (I) 2x + y = 13 ... (II) Multiply both sides of equation (II) by 3 6x + 3y = 39 ... (III) Add equations (I) and (II) 2x - 3y = 9 +6x + 3y = 39 ----------------------------- 8x = 39 Substituting x = 6 in equation (II) 2x + y = 13 ? 2(6) + y = 13 ? y = 13 - 12 ? y = 1 x = 6, y = 1 is the solution.
SÉå cÉUÉÇMüÉåÇ uÉÉsÉå UåZÉÏrÉ xÉqÉÏMüUhÉ June 22 , 2018 0 Comments 21 views